An Analysis of Sign Language Features Used by Eliza in the Shape of Water Film - Surahman, Dian Purnama; Ariani, Setya; Valiantien, Nita Maya (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
This study aims to understand the features of sign language used by Eliza in The Shape of Water film. The researchers analyzed the use of sign language used by a mute adult woman named Elisa based on the film The Shape of Water. This study focuses on the features of sign language used by Elisa to communicate with people in the film. The approach used in this research is the qualitative approach and content analysis design. In conducting this research, the main theory is Sign Language features by Gallaudet. This study found several sign language features used by Elisa to help her communicate, such as hand shape, palm orientation, placement, non-manual features, and hand movement. This research will make people get more understand sign language and how to use sign language, moreover this research could bring awareness to communicating with deaf and mute people.